2013
DOI: 10.1002/jms.3176
|View full text |Cite
|
Sign up to set email alerts
|

UFLC–MS/MS method for simultaneous determination of six lignans of Schisandra chinensis (Turcz.) Baill. in normal and insomniac rats brain microdialysates and homogenate samples: towards an in‐depth study for its sedative‐hypnotic activity

Abstract: Schisandra chinensis (Turcz.) Baill., a traditional Chinese medicine, has been clinically used for the treatment of insomnia for centuries. The insomnia mechanism and the possible active ingredients of S. chinensis remain largely unknown. The objective of this study was to develop a method to detect its components which could pass through the blood brain barrier (BBB) by determining the brain microdialysate and brain tissue homogenate samples and then obtain the pharmacokinetic profile in brain for comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
(29 reference statements)
0
18
0
Order By: Relevance
“…For example, the typical lignan honokiol is able to cross the BBB and the blood-cerebrospinal fluid barrier, and it exerts an anticancer effect [47,48]. Furthermore, six lignans have been detected directly in rat brain tissue after oral administration of lignan extracts [49]. Therefore, the present investigations showed that lignans have the greatest potential for crossing the BBB and modulating the nervous system via a 5-HT1AR agonist-like mechanism.…”
Section: Discussionmentioning
confidence: 77%
“…For example, the typical lignan honokiol is able to cross the BBB and the blood-cerebrospinal fluid barrier, and it exerts an anticancer effect [47,48]. Furthermore, six lignans have been detected directly in rat brain tissue after oral administration of lignan extracts [49]. Therefore, the present investigations showed that lignans have the greatest potential for crossing the BBB and modulating the nervous system via a 5-HT1AR agonist-like mechanism.…”
Section: Discussionmentioning
confidence: 77%
“…The newest methods applied to determine lignans are: ultra-performance liquid chromatography (UPLC) (Guo et al 2012; Kim et al 2014b; Sun et al 2013b; Yan et al 2014; Zhou et al 2011) and ultra-fast liquid chromatography (UFLC) (Wei et al 2013). Both techniques provide better possibilities than in HPLC but obtained in different ways.…”
Section: Analytical Methods In Determination Of Dibenzocyclooctadienementioning
confidence: 99%
“…Blood–brain barrier (BBB) is a main obstacle to the effective delivery of drugs to the brain, which directly impacts on the efficacy of drugs. Previous study showed that the amount of SCH‐C could be detected in rat brain was very low (0.17 ng/mL in brain homogenate) after oral administration (Wei et al ., ). Our view was that compared with the peripheral administration, SCH‐C injected directly into the brain may lead to a better bioavailability and consequently a more potent neuroprotective effect in brain.…”
Section: Discussionmentioning
confidence: 99%